Engineering inorganic hybrid nanoparticles : tuning combination fashions of gold, platinum, and iron oxide - Zhang, Hai Tao (2011)
Multistep colloidal chemical routes were employed to synthesize Pt/Au, Pt/iron oxide (IO), and Au/Pt/IO hybrid nanoparticles (NPs). The starting templates, Pt NPs, were synthesized by controlling the decomposition kinetics of platinum acetylacetonate in oleylamine. The morphologies of binary metal Pt/Au hybrid NPs were modulated by controllable attachment of Au nanoscale domains to Pt templates. Similarly, Pt/IO and Au/Pt/IO hybrid NPs were fabricated by the controllable attachment of Fe to the Pt or Pt/Au template NPs. The noble metal domains of as-prepared hybrid NPs had face center cubic crystal structures and did not alloy, as verified by high resolution transmission electron microscopy and X-ray diffraction spectrometry. X-ray diffraction spectrometry study indicates that the IO domains in the as-prepared NPs have a spinel structure. UV−vis study of binary metal Pt/Au hybrid NPs revealed that they have a characteristic plasmon resonance around 525 nm, while dumbbell-like Au/Pt/IO NPs had a plasmon resonance around 600 nm. Furthermore, magnetism study of the binary Pt−IO NPs clearly indicated that the interfacial interactions between Pt and IO domains could result in a shift of the blocking temperature.